EXISTENCE: WHO NEEDS IT? THE NON-IDENTITY PROBLEM AND MERELY POSSIBLE PEOPLE - Weinberg, Rivka (Bioethics, 2013)
In formulating procreative principles, it makes sense to begin by thinking about whose interests ought to matter to us. Obviously, we care about those who exist. Less obviously, but still uncontroversially, we care about those who will exist. Ought we to care about those who might possibly, but will not actually, exist? Recently, unusual positions have been taken regarding merely possible people and the non-identity problem. David Velleman argues that what might have happened to you – an existent person – often doesn't merit moral consideration since the alternative person one would have been had what might have happened actually happened is a merely possible person about whom one has no reason to care. He argues that his way of thinking can eliminate the non-identity problem. Caspar Hare argues that merely possible people have interests and are morally relevant. He argues that we can solve the non-identity problem by rejecting the view that merely possible people are morally irrelevant. Both Hare and Velleman argue that focusing on one's de dicto rather than on one's de re children can help us avoid the non-identity problem. I analyze the role that merely possible, nonexistent hypothetical entities ought to play in our moral reasoning, especially with regard to procreation. I refute both Velleman's and Hare's views and demonstrate the difficulties we encounter when we try to apply their views to common non-identity cases. I conclude with the common-sense view regarding who matters, morally: only those who do, did, or will exist.